(untitled) - Valovicova, Stanislava (Doprava a spoje, 2005)
This article deals with the methods for multicriterial assessment and their application. I proposed how to use these methods in the field of quality of services and its measurement, first of all in term of competitive analysis. I focused on my own methodical proposal leading to calculation of the numerical order of the selected service providers according to the specific evaluative criteria. Thanks to the method application it will be possible to specify the key factors, which influenced the research results in comparison with the services of competitors and consequently to define an effective competitive strategy.